Growth Factors Outside the PDGF Family Drive Experimental PVR - Lei, Hetian (2009)
PURPOSE: Proliferative vitreoretinopathy (PVR) is a recurring and problematic disease for which there is no pharmacologic treatment. Platelet-derived growth factor (PDGF) in the vitreous is associated with experimental and clinical PVR. Furthermore, PDGF receptors (PDGFRs) are present and activated in epiretinal membranes of patient donors, and they are essential for experimental PVR. These observations suggest that PVR arises at least in part from PDGF/PDGFR-driven events. The goal of this study was to determine whether PDGFs were a potential therapeutic target for PVR. METHODS: Experimental PVR was induced in rabbits by injecting fibroblasts. Vitreous specimens were collected from experimental rabbits or from patients undergoing vitrectomy to repair retinal detachment. A neutralizing PDGF antibody and a PDGF Trap were tested for their ability to prevent experimental PVR. Activation of PDGFR was monitored by antiphosphotyrosine Western blot analysis of immunoprecipitated PDGFRs. Contraction of collagen gels was monitored in vitro. RESULTS: Neutralizing vitreal PDGFs did not effectively attenuate PVR, even though the reagents used potently blocked PDGF-dependent activation of the PDGF α receptor (PDGFRα). Vitreal growth factors outside the PDGF family modestly activated PDGFRα and appeared to do so without engaging the ligand-binding domain of PDGFRα. This indirect route to activate PDGFRα had profound functional consequences. It promoted the contraction of collagen gels and appeared sufficient to drive experimental PVR. CONCLUSIONS: Although PDGF appears to be a poor therapeutic target, PDGFRα is particularly attractive because it can be activated by a much larger spectrum of vitreal growth factors than previously appreciated.